2000
DOI: 10.1016/s0304-3959(00)00349-3
|View full text |Cite
|
Sign up to set email alerts
|

In vivo pharmacology of SDZ 249-665, a novel, non-pungent capsaicin analogue

Abstract: Capsaicin and analogues are valuable analgesic agents when administered to mammals, including humans. However, their pungency and the effects on the cardiovascular and respiratory systems through their general activation of small calibre (nociceptive) primary afferents severely limit their use. Recently, structure activity analysis revealed that the initial pungent and general excitatory effects can be prevented by structural modifications in such a way that the analgesic activity is retained. In this paper we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 25 publications
0
46
0
1
Order By: Relevance
“…For example, the half-maximal concentrations (EC 50 ) of capsaicin for activating native capsaicin- sensitive currents is ϳ0.68 -1.1 M (Liu and Simon, 1996;Oh et al, 1996;Koplas et al, 1997;Liu et al, 1997;Jung et al, 1999). In contrast, EC 50 values for activating TRPV1 expressed in mammalian cell lines are 0.1-0.25 M, much lower than those for native capsaicin-sensitive currents in sensory neurons (Tominaga et al, 1998(Tominaga et al, , 2001Mohapatra and Nau, 2003 Wood et al, 1988;Cholewinski et al, 1993;Urban et al, 2000), whereas those in HEK-TRPV1 or CHO-TRPV1 cells are 0.016 -0.098 M (Gavva et al, 2004;Toth et al, 2004). The difference in potency stems from variation possibly raised by different experimental procedures performed in different laboratories.…”
Section: Discussionmentioning
confidence: 98%
“…For example, the half-maximal concentrations (EC 50 ) of capsaicin for activating native capsaicin- sensitive currents is ϳ0.68 -1.1 M (Liu and Simon, 1996;Oh et al, 1996;Koplas et al, 1997;Liu et al, 1997;Jung et al, 1999). In contrast, EC 50 values for activating TRPV1 expressed in mammalian cell lines are 0.1-0.25 M, much lower than those for native capsaicin-sensitive currents in sensory neurons (Tominaga et al, 1998(Tominaga et al, , 2001Mohapatra and Nau, 2003 Wood et al, 1988;Cholewinski et al, 1993;Urban et al, 2000), whereas those in HEK-TRPV1 or CHO-TRPV1 cells are 0.016 -0.098 M (Gavva et al, 2004;Toth et al, 2004). The difference in potency stems from variation possibly raised by different experimental procedures performed in different laboratories.…”
Section: Discussionmentioning
confidence: 98%
“…Anandamide was originally isolated from porcine brain as the first endogenous cannabinoid (Devane et al, 1992), and its biosynthesis has subsequently been demonstrated in neurons (Di Marzo et al, 1994), macrophages (Di Marzo et al, 1996), and recently in lung (Calignano et al, 2000). In contrast to capsaicin, anandamide and the synthetic vanilloids and analgesic agents olvanil and SDZ 249 -665 do not induce airway obstruction in vivo (Wrigglesworth et al, 1996;Stengel et al, 1998;Calignano et al, 2000;Urban et al, 2000). Consistent with these observations, recent studies suggest that anandamide is a weak constrictor of isolated airways compared with capsaicin Tucker et al, 2001).…”
mentioning
confidence: 81%
“…In some animals, capsaicin was subcutaneously administered in three divided doses (50 and 25 mg/kg on the first day and 50 mg/kg on the second day) over a 2-day period to desensitize the majority of C-fiber afferents that are sensitive to capsaicin 5 days before cystometry (47). C-fiber desensitization was confirmed by negative response to an eye wipe test before the experiments (53).…”
Section: Methodsmentioning
confidence: 99%